Performance evaluation of PDMS or PEBAX- coated polyetherimide membrane for oxygen/nitrogen separation - Chong, Kok Chung; Lai, Soon Onn; Thiam, Hui San; Mah, Shee Keat; Lau, Woei Jye; Ahmad Fauzi Ismail (Penerbit Universiti Kebangsaan Malaysia, 2021)
Since the industrial revolution era, the Earth was suffering from serious air pollution. Millions of people are now suffering from indoor air pollution related diseases, especially in the industrialized countries such as China. One method to improve the indoor air quality is by oxygen enhancement. Membrane technology has been a key research over the past decades due to its low energy usage, minimum chemical consumption as well as small setting up layout. In this study, polyetherimide (PEI) membranes coated with polydimethylsiloxane (PDMS) or poly(ether block amide) (PEBAX) at different concentration (1, 3 or 5 wt%) were used to evaluate the oxygen/nitrogen gas separation. Prior to the gas permeation study, the membranes were characterized using scanning electron microscope (SEM) for morphology observation and surface elemental analysis by energy dispersive X-ray spectroscope (EDX). The morphology of the self-fabricated PEI membranes is composed of a thin and dense structure supported by the finger-like structure. The results obtained from oxygen/nitrogen separation studies shows membrane coated with 3 wt% PDMS yield a good separation results, exhibiting an improvement of oxygen and nitrogen permeance by 28.2% and 24.9%, selectivity by 10.4% (up to 5.08) relative to the base PEI membrane. Meanwhile, the 3 wt% PEBAX-coated PEI membrane only achieved selectivity of 3.56. The PDMS-coated PEI membrane yield a better separation performance attributed to the fact that PDMS coating on the hollow fiber membrane improve the surface morphology by reducing the defects.